Problems of cancer-related pain control in the practice of a clinical oncologist - Krzemieniecki, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2005)
Chronic pain, especially cancer-related pain, lost its physiologic alerting function. Its chronic characteristic is related to a diminished patient performance status, degradation of social and professional position as well as psychological disorders (anxiety, depression, sleeplessness). Patients have the right to have their pain treated effectively and it is one of the major physicians’ commitments. There are data about insufficient pain control in many countries despite of the fact that general practitioners and clinical oncologists are able to effectively treat pain in 80% of the cases. The myths on opioids’ use (addiction, very toxic side effects, and the early lack of treatment efficacy) are listed among the main causes of inappropriate pain treatment. The understanding of pain ethiopathogenesis is the key to successful therapy, which is not obvious for all physicians. Inappropriate physician-patient relations are another obstacle to optimal treatment. Dynamic characteristic of cancer pain and changing patient needs require very strict treatment monitoring. New drug technologies (retard formulation, TTS system) improve patients’ compliance and treatment efficacy. A postgraduate education program on pain control and modern analgesic medications may help treat almost 80% of patients with cancer-related pain in an easy, comfortable and successful manner.